Reforma al art. 36 de la Ley de Régimen Tributario Interno, referente a la base imponible del impuesto a la renta de personas naturales y sucesiones indivisas - Aldás Tandalia, Nelly Marina (2015)
Capital or income comes from labor and capital, standing in money, species or services, which is deducted from the profits received during the calendar year, taking into account discounts dependents as long as it is under responsibility taxpayer, by which the tax is paid by the product and received profits taking into consideration the capital. The income tax to be a direct tax that affects the assets accruing to natural persons, undivided estates during the year, after deducting the costs and expenses incurred are calculated considering the taxable amount determined by law. The volume of the fiscal deficit in our country is mainly linked with tax evasion by taxpayers; considered illegitimate act of tax evasion as an act of intelligence. Although lately with the actions taken by the State; They have raised the percentage of tax collection; still it continues to show a percentage of escape, through different ways; One is the non-declaration of income tax; which probably it is summarized in a breach of obligations of individuals; also it stems from the same system of determination and declaration of income tax. The current progressive system of income tax represents a heavy burden for most endeavors and produces, as it takes away a larger share of the fruits of their labor, so as a way to improve the collection of resources for the Treasury, It is to replace the income tax with a flat tax or single rate that allows for equal treatment to all people and that promotes efficiency in the collection of the tax. The problem is identified has to do with the progressivity of the income tax, since its implementation has meant a disincentive to work, productivity and innovation of Ecuadorians, to punish by extracting a higher proportion of the fruit of their work to strives more and produce. Also this escalation violates the principle of equality of all before the law established in the Constitution. For this consideration I felt that the Income Tax conceived in our legal system as a progressive tax should be replaced by a flat tax many gains would come primarily impartiality so that workers and successful businessmen will not be hardest hit by discriminatory tax rates, which would promote faster economic development; allow equal treatment among taxpayers; and increase the amounts of revenue